Exploring the antibacterial potential of arthrocolins against extensively drug-resistant Pseudomonas aeruginosa: mechanistic insights into amino acid metabolism disruption - Yang, Bao-Rui; Zhang, Yun-Wen; Wu, Qun-Fu; Liu, Jian-Mei; Wu, Guang-Juan; Tian, Wei-Juan; Deng, De-Yao; Niu, Xue-Mei; Yuan, Wen-Li (Frontiers in Microbiology, 2025)
IntroductionExtensively drug-resistant Pseudomonas aeruginosa (XDR-PA) poses a serious clinical threat due to its intrinsic resistance mechanisms and the lack of effective therapeutic agents. This study aimed to evaluate the antibacterial activity of arthrocolins (Acs), a novel group of xanthene-like compounds isolated from Escherichia coli, against XDR-PA.MethodsClinical data analysis was conducted to identify significant risk factors for XDR-PA infection. Drug susceptibility testing was performed to assess the effectiveness of Acs. Transmission electron microscopy (TEM) was used to observe cellular changes in Acs-treated bacteria, while integrated transcriptomic and metabolomic analyses were employed to investigate the underlying mechanisms.ResultsAcs demonstrated significant antibacterial activity, inhibiting XDR-PA growth at low micromolar concentrations. The IC50 value was determined to be 3.094 μM. Clinical data analysis identified prolonged antimicrobial therapy, invasive procedures, and extended hospitalization as significant risk factors for XDR-PA infection. TEM revealed cell wall disruption and cytoplasmic condensation in Acs-treated bacteria. Integrated omics analyses indicated that Acs interferes with amino acid metabolism, impairing energy production and causing abnormal lipid accumulation.DiscussionThese findings suggest that Acs exerts potent antibacterial effects through disruption of metabolic homeostasis and structural integrity. The study highlights the potential of Acs as a promising candidate for the treatment of XDR-PA infections, offering a new avenue for therapeutic development. The bacterial names cannot be italicized in the annotations. The revised abstract has been uploaded separately as an attachment.